2018
DOI: 10.1088/1748-605x/aab0b3
|View full text |Cite
|
Sign up to set email alerts
|

Engineering principles for guiding spheroid function in the regeneration of bone, cartilage, and skin

Abstract: There is a critical need for strategies that effectively enhance cell viability and post-implantation performance in order to advance cell-based therapies. Spheroids, which are dense cellular aggregates, overcome many current limitations with transplanting individual cells. Compared to individual cells, the aggregation of cells into spheroids results in increased cell viability, together with enhanced proangiogenic, anti-inflammatory, and tissue-forming potential. Furthermore, the transplantation of cells usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 132 publications
(268 reference statements)
2
57
0
Order By: Relevance
“…Particle sizes up to 200 µm can be considered the most relevant for studying cell seeding as this range allows the use of small cell aggregates for seeding as well. Dense cell aggregates, or spheroids, are known to result in increased tissue formation and cell viability compared with individual cells [34,35]. For comparison, in a previous report, the size of fixed hASCs ranged from 5 to 40 µm with an average diameter of 22 µm [36].…”
Section: Discussionmentioning
confidence: 96%
“…Particle sizes up to 200 µm can be considered the most relevant for studying cell seeding as this range allows the use of small cell aggregates for seeding as well. Dense cell aggregates, or spheroids, are known to result in increased tissue formation and cell viability compared with individual cells [34,35]. For comparison, in a previous report, the size of fixed hASCs ranged from 5 to 40 µm with an average diameter of 22 µm [36].…”
Section: Discussionmentioning
confidence: 96%
“…Cell‐rich 3D clusters fabrication takes advantage of intercellular adhesion mechanisms (e.g., cadherin and integrin‐mediated) to create self‐assembled structures comprising single, or multiple cell types, unlocking the potential to fabricate heterotypic cell constructs more similar to the cellular heterogeneity of human tissues . Upon in vitro maturation, these seamless 3D microaggregates secrete de novo ECM frameworks in which cells reside and exchange interactions, adding to their biofunctionality and biomedical applicability.…”
Section: Cell‐rich Assembliesmentioning
confidence: 99%
“…To date, advanced monotypic (single culture) and heterotypic (co‐culture) scaffold‐free 3D multicellular spheroids have been developed as in vitro microphysiological systems for modeling pathophysiology of human diseases or as unitary building blocks for tissue engineering of cardiac, hepatic, vascular, or neuronal tissues, among others . In the context of tissue engineering and regeneration, 3D spheroids have been employed as angiogenic stimulating units (i.e., via secretion of trophic factors—VEGF, PDGF) or as functional blocks for the assembly of prevascularized microtissues . Progresses in this field indicate that 3D spheroids comprising heterogeneous cell populations better recapitulate the complexity of human tissues and exhibit a more pro‐regenerative capacity.…”
Section: Cell‐rich Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bee pollen are consumed as functional foods because it contains numerous nutrients, vitamins and minerals [36,37]. Numerous studies have reported that bee pollen contains phenolic acids, kaempferol, palmitic, linoleic acids, calcium, sodium, potassium, and vitamin B, C and E [38,39]. Bee pollen has been studied in apitherapy which is a branch of alternative medicine that mainly uses honey bee products such as honey, pollen, bee venom, etc.…”
Section: Bee Collected Pollenmentioning
confidence: 99%